Managing service level agreement contracts in OGSA-based Grids - Chatzis, Sotirios P.; Litke, Antonios; Konstanteli, Kleopatra; Andronikou, Vassiliki; Varvarigou, Theodora (My University, 2008)
Grids and mobile Grids can form the basis and the enabling technology for pervasive and utility computing due to their ability to be open, highly heterogeneous and scalable. However, the process of selecting the appropriate resources and initiating the execution of a job is not enough to provide quality in a dynamic environment such as a mobile Grid, where changes are numerous, highly variable and with unpredictable effects. In this paper we present a scheme for advancing and managing Quality of Service (QoS) attributes contained in Service Level Agreement (SLA) contracts of Grids that follow the Open Grid Services Architecture (OGSA). In order to achieve this, the execution environment of the Grid infrastructure establishes and exploits the synergies between the various modules of the architecture that participate in the management of the execution and the enforcement of the SLA contractual terms. We introduce an Execution Management Service which is in collaboration with both the application services and the network services in order to provide an adjustable quality of the requested services. The components that manage and control the execution in the Grid environment interact with the suit of the SLA-related services exchanging information that is used to provide the quality framework of the execution with respect to the agreed contractual terms. The described scheme has been implemented in the framework of the Akogrimo IST project
Keywords: Computer systems; Computational grids (Computer systems); Computer architecture; Utilities (Computer programs)